Hyperintense Vessels, Collateralization, and Functional Outcome in Patients With Stroke Receiving Endovascular Treatment. Issue 3 (March 2018) - Nave, Alexander H.; Kufner, Anna; Bücke, Philipp; Siebert, Eberhard; Kliesch, Stefan; Grittner, Ulrike; Bäzner, Hansjörg; Liebig, Thomas; Endres, Matthias; Fiebach, Jochen B.; Nolte, Christian H.; Ebinger, Martin; et al.
Abstract : Background and Purpose—: Fluid-attenuated inversion recovery hyperintense vessels (FHV) are frequently observed on magnetic resonance imaging in acute stroke patients with proximal vessel occlusion. Whether FHV can serve as a surrogate for the collateral status and predict functional outcome of patients is still a matter of debate. Methods—: Acute ischemic stroke patients with M1-middle cerebral artery occlusion who received magnetic resonance imaging before endovascular treatment in 3 hospitals in Germany between January 2007 and June 2016 were eligible. Quantification of FHV was performed using an FHV–Alberta Stroke Program Early CT Score (ASPECTS) rating system. Functional outcome was evaluated with the modified Rankin Scale 3 months after stroke. Collateral status of patients was graded on baseline angiography using the American Society of Interventional and Therapeutic Neuroradiology grading system. Odds for good outcome (modified Rankin Scale score, 0–2) were determined using logistic regression analyses. Results—: Overall, 116 patients were analyzed (median age, 74; interquartile range [IQR], 64–79; median National Institutes of Health Stroke Scale, 14; IQR, 10–19). The median FHV-ASPECTS was 2 (IQR, 1–3). Good collateral status (American Society of Interventional and Therapeutic Neuroradiology grade 3–4) on angiography was more frequently observed in patients with FHV-ASPECTS ⩽2 (83% versus 57%; P =0.025). Patients with an FHV-ASPECTS ⩽2 had a better functional outcome after 3 months (median modified Rankin Scale score, 2; IQR, 0–5), compared with patients with an FHV-ASPECTS >2 (median modified Rankin Scale score, 4; IQR, 3–6; P =0.015). In multiple regression analyses, FHV-ASPECTS ⩽2 was independently associated with good functional outcome (adjusted odds ratio, 5.3; 95% confidence interval, 1.5–18.2). Conclusions—: Low FHV-ASPECTS is associated with both better collateral status and better 3-month functional outcome in acute stroke patients with M1 vessel occlusion. Abstract : Supplemental Digital Content is available in the text.